$\bf命题:$设$A \in {M_{m \times n}}\left( F \right),B \in {M_{n \times m}}\left( F \right),m \ge n,\lambda \ne 0$,则
\[{\rm{ }}\left| {\lambda {E_m} - AB} \right| = {\lambda ^{m - n}}\left|
{\lambda {E_n} - BA} \right|\]
方法一:初等变换法
\[\left(
{\begin{array}{*{20}{c}}
{\lambda
{E_m}}&A\\
B&{{E_n}}
\end{array}} \right) \to \left(
{\begin{array}{*{20}{c}}
{\lambda {E_m} -
AB}&0\\
B&{{E_n}}
\end{array}} \right) \to \left(
{\begin{array}{*{20}{c}}
{\lambda {E_m} -
AB}&0\\
0&{{E_n}}
\end{array}} \right)\]
\[\left(
{\begin{array}{*{20}{c}}
{\lambda
{E_m}}&A\\
B&{{E_n}}
\end{array}} \right) \to \left(
{\begin{array}{*{20}{c}}
{\lambda {E_m}}&A\\
0&{\frac{1}{\lambda
}\left( {\lambda {E_n} - BA} \right)}
\end{array}} \right) \to \left(
{\begin{array}{*{20}{c}}
{\lambda {E_m}}&0\\
0&{\frac{1}{\lambda
}\left( {\lambda {E_n} - BA} \right)}
\end{array}} \right)\]
方法二:等价标准形
由$r\left( A \right) = r$知,存在可逆阵$P,Q$,使得
\[PAQ = \left(
{\begin{array}{*{20}{c}}
{{E_r}}&0\\
0&0
\end{array}}
\right)\]令\[{Q^{ - 1}}B{P^{ - 1}} = \left(
{\begin{array}{*{20}{c}}
{{B_1}}&{{B_3}}\\
{{B_4}}&{{B_2}}
\end{array}}
\right)\]
其中${B_1}$为$r \times r$矩阵,于是有
\[PAB{P^{ - 1}} = PAQ \cdot {Q^{ -
1}}B{P^{ - 1}} = \left(
{\begin{array}{*{20}{c}}
{{B_1}}&{{B_3}}\\
0&0
\end{array}}
\right)\]
且\[{Q^{ - 1}}BAQ = {Q^{ - 1}}B{P^{ - 1}} \cdot PAQ = \left(
{\begin{array}{*{20}{c}}
{{B_1}}&0\\
{{B_4}}&0
\end{array}}
\right)\]
从而可知
\[\left| {\lambda {E_m} - AB} \right| = \left|
{\begin{array}{*{20}{c}}
{\lambda {E_r} - {B_1}}&{ -
{B_3}}\\
0&{\lambda {E_{m - r}}}
\end{array}} \right| = {\lambda ^{m -
r}}\left| {\lambda {E_r} - {B_1}} \right|\]
且\[\left| {\lambda {E_n} - BA}
\right| = \left| {\begin{array}{*{20}{c}}
{\lambda {E_r} -
{B_1}}&0\\
{ - {B_4}}&{\lambda {E_{n - r}}}
\end{array}} \right| =
{\lambda ^{n - r}}\left| {\lambda {E_r} - {B_1}} \right|\]
故结论成立
$\bf注1:$命题中的结论称为$\bf行列式的降阶公式$
$\bf注2:$$\left| {\lambda {E_m} - AB} \right| = \left| {{P^{ - 1}}} \right| \cdot \left| {\lambda {E_m} - AB} \right| \cdot \left| P \right| = \left| {{P^{ - 1}}\lambda {E_m}P - {P^{ - 1}}ABP} \right| = \left| {\lambda {E_m} - {P^{ - 1}}ABP} \right|$
原文:http://www.cnblogs.com/ly142857/p/3674031.html